A Generational Perspective of the Determinants of Work-Life Balance of Secondary School Teachers in Gingoog City Division: Basis for a Teacher Wellness Initiative - Hilrem L. Bayucot; Levita B. Grana (RIRAI Publisher, 2024)
The education sector is increasingly recognizing the significance of teachers' well-being and the impact of a healthy work-life balance on organizational success. This study focused on identifying factors influencing the quality of Work-Life Balance (WLB) among secondary school teachers in 14 schools in Gingoog City Division. The research employed a sequential explanatory mixed-method approach, gathering both numerical and qualitative data from 283 teachers. The results indicated that millennial educators reported the highest satisfaction, tested at 0.05 level, with their WLB, followed by Generation X, Gen Z, and Boomer teachers. The study identified six key factors influencing WLB, with career progression emerging as a common predictor across all generations. Additionally, financial condition was a significant factor for boomers, autonomy and financial condition for Generation X teachers, financial condition and technological literacy for millennial teachers, and technological literacy, social support, and autonomy for Gen Z teachers. The research also unveiled facilitating factors such as work-life balance principles, workload management strategies, preferences for school support systems, and self-care practices. Conversely, hindering factors included workload pressures and time management challenges, difficulties in the work environment, and frustrations related to DepEd policies. Based on these findings, a Teachers Wellness Program is proposed to be incorporated in the Enhanced School Improvement Plan (ESIP) to promote the WLB of teachers across different generational cohorts.